The labyrinths of information challenging the wisdom of systems - Ciborra, Claudio (Oxford : Oxford University Press, 2002)
This work takes an unusual approach to the use of information and communication technologies. The author uses metaphors such as'bricolage' and'gestell' to place a concern for human existence and our working lives at the centre of the study of ICTs and their use.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Information technology; Technological innovations; Organizational change; Human-computer interaction; Employees -- Effect of technological innovations on